Unravelling spermatogenesis in spotted wolffish: Insights from the ultrastructure of juvenile male testes to the cryopreservation of broodstock sperm - Superio, Joshua; Resseguier, Julien; Nobrega, Rafael Henrique [UNESP]; Grebstad, Caroline M.; Fakriadis, Ioannis; Foss, Atle; Hagen, Ørjan; Zhang, Meiling; del Pilar García-Hernández, Maria; Galindo-Villegas, Jorge (Elsevier, 2024)
The aim of this study was to deepen our understanding of the reproductive biology of male spotted wolffish (Anarhichas minor) using two different experimental approaches involving juvenile and mature broodstock fish. The first approach consisted of a detailed histological examination of the testes to identify the onset of gonadal maturation and characterise the spermatogenic stages in two- and three-year-old juvenile specimens. Light microscopy analysis revealed clear differences between the age groups. Two-year-old fish displayed well-defined interstitial tissue, Sertoli cells and cysts housing spermatogonia stem cells in which meiosis had not yet begun. In contrast, three-year-old fish exhibited cysts containing spermatocytes, spermatids and abundant spermatozoa, indicating the initiation of the spermatogenic cycle, albeit with asynchronous puberty. Histochemical staining revealed a significant presence of smooth myoid cells in the interstitial tissue of sexually mature fish, while electron microscopy further revealed synaptonemal complexes indicating the onset of meiosis and centriolar structures that gave rise to flagella. The second approach focused on optimising semen freezing and cryopreservation procedures in mature broodstock individuals over the age of 10 years. Seven freezing extenders (KT, TS-2, OP, MT, MH, HBSS, or SR), with seawater (SW) as a control, were assessed along with two cryoprotectants dimethylsulfoxide (DMSO) or methanol to evaluate their impact on pre- and post-thaw semen quality. Results showed that the MT and HBSS extenders were superior in total sperm kinetics at 1:3 dilution, and that DMSO showed optimal results in sperm motility and velocity variants. Moreover, the MT and HBSS groups demonstrated consistent sperm viability after cryopreservation, with values similar to fresh samples. Based on the viability results of the SYBR-green-14/PI assay comparing fresh and cryopreserved sperm using MT and HBSS, the MT extender emerged as the most effective freezing medium for cryopreservation of spotted wolffish broodstock sperm. In conclusion, this study provides a comprehensive understanding of the reproductive dynamics of male spotted wolffish, offering valuable insights for both scientific research and aquaculture management.
Keywords: Anarhichas minor; CASA; Cryopreservation; Emerging teleost species; Extenders; Phalloidin; Spermatogenesis